Variation of Word Nn in Sumbawa Language - Wirentake (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2022)
Samawa language is a regional language in west Sumbawa Island supported by the great majority of speech community. Those communities indicate the function of Samawa language function as their identity, symbol of culture values and unifying community forces. This study carries out a simple investigation on Samawa language, especially, on the construction of negative-marker “No” and its variations to know how far its uniqueness as a means of negation. In general, this study tries to describe the construction of negative-marker “no” of Samawa language by using a set of linguistic theory, especially, concerning with syntactical unit at the place of negation. This study employs descriptive research which aims to give the description about “variation of words “no” in Samawa language systematically, factually, and accurately. The subject of this study is Samawa language as a regional language and Samawa Rea dialect used by Samawa ethnics people where there the respondents are taken from Sumbawa native speakers itself. The results are then further discussed.